Modulation of Heart Rate Variability in Stressed Medical Students Via Breathing Exercise - Noman Sadiq, Tahira Sadiq, Wazir Ahmed Baloch, Humaira Fayyaz Khan, Noor Nasir Rajpoot, Shazia Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Stress in medical students is a global concern. Stress disturbs the sympathovagal balance and affects heart rate variability, a sign of healthy cardiovascular homeostasis. Various strategies have been used globally to combat stress and its effects. Aim: To determine how blowing balloon exercise modulatesheart rate variability (HRV) in stressed medical students. Methodology: A pretest-posttest quasi-experimental study wasconducted among stressed medical students at Islamic international medical college Rawalpindi Pakistan. Sixty students diagnosed with moderate stress were enrolled based on Depression Anxiety Stress Scale (DASS) Proforma. The study population was selected by simple random sampling via the balloting method among the stressed medical students. Study participants underwent a supervised blowing balloon exercise.Before and after a supervised blowing balloon exercise, the participants’ pulmonary function tests, electrocardiograms, and DASS scores were measured. Participants’ ECGs and pulmonary function tests were recorded viaPower lab (A.D. Instruments, model yam 4/25T, South Wales, Australia). Results: Blowing balloon exercise resulted in a significant reduction of DASS score (p<0.001) and significant improvement in pulmonary function tests (p<0.001). Among Heart rate variability parameters, the participants’ standard deviation of successive N-N intervals, high-frequency components, and high-frequency normalized units significantly increased (p<0.05) after blowing balloon exercise. Heart rate, low-frequency normalized units, and the ratio of low-frequency normalized value to high-frequency normalized value were significantly reduced (p<0.05) after blowing balloon exercise. Conclusions: Blowing balloon exercise enhances medical students’ heart rate variability and pulmonary function tests while reducing their stress levels. This cost-effective and easy exercise can be performed by stressed students without any time or place barrier. Keywords: Anxiety, Breathing Exercise, Depression, Heart Rate Variability, Stress, Sympathovagal Balance.